Effects of pattern masks on the formation of perceptual grouping - Kurylo, Daniel D.; Bukhari, Farhan (Vision research (Oxford), 2017)
•Masks superimposing element grids disrupts grouping for 12ms following target offset.•Masking regions among elements disrupts grouping for 47ms following target offset.•Time-scale of grouping formation increases with reduced organization of the stimulus. Mechanisms underlying perceptual grouping serve to bind stimulus components that are contained within grouped patterns. In order to examine the time course of grouping development, grids of spatially isolated dots were followed by pattern masks across a range of SOA. Subjects indicated the predominant perceived grouping of the dot patterns. Masks either spatially superimposed target elements (element mask), or superimposed elements as well as paths among elements (connection mask). Element masks thereby disrupted processing of target elements, while connection masks additionally disrupted representations in regions among elements. It was found that element masks disrupted grouping 12ms after target offset, after which masks had no effect. Connection masks disrupted grouping up to 47ms following target offset. Results suggest grouping mechanisms access the afferent signal for a brief period early in processing, after which binding formation proceeds for an addition 35ms. Shortening connection mask duration to 12ms enhanced performance during a brief temporal window within the interference period. For each set of conditions, target elements were visible during the time frame in which stimulus patterns could not be perceptually grouped. Full-field checkerboard masks degraded discrimination similarly as connection masks, although were more effective in disrupting discrimination with an SOA of 24 and 36ms. Degrading stimulus organization progressively extended the time scale for each masking effect. For the grouping of low-level stimulus features tested here, results support a model in which afferent signals are accessed early, followed by progressive binding among grouped elements. Effect of shortening connection masks may reflect incomplete disruption of target processing, or possibly re-entry of stimulus representations by feedback from higher processing areas.